2014
DOI: 10.1007/s11434-014-0535-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetic status of Siberian roe deer (Capreolus pygargus) based on mitochondrial cytochrome b from Jeju Island in Korea

Abstract: In order to elucidate the genetic diversity and taxonomic status of Siberian roe deer (Capreolus pygargus) from the Korean peninsula, partial sequences of the mitochondrial cytochrome b gene were analyzed. We collected 57 roe deer samples from Mainland and Jeju Island between July 2004 and June 2009. A total of 50 sequences (1,070 bp) were obtained, and seven haplotypes were defined. Five haplotypes were found from Mainland, and two were discovered from Jeju Island. The genetic diversity was lower in the Jeju … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…p. tianschanicus (Koh, Yang, Yoo, & Chun, ), nor as a distinct subspecies as suggested by Koh and Randi () and Park et al. (). Siberian roe deer from Jeju Island are indeed different from those of mainland Korea (Lee et al., ), but they do not appear to represent a distinct phylogenetic clade, sharing the main haplogroup of Western populations.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…p. tianschanicus (Koh, Yang, Yoo, & Chun, ), nor as a distinct subspecies as suggested by Koh and Randi () and Park et al. (). Siberian roe deer from Jeju Island are indeed different from those of mainland Korea (Lee et al., ), but they do not appear to represent a distinct phylogenetic clade, sharing the main haplogroup of Western populations.…”
Section: Discussionmentioning
confidence: 82%
“…Our results raise questions about the taxonomic status of the Siberian roe deer inhabiting Jeju Island, which was composed of only one haplogroup (cluster B). Genetic distinction (pairwise F ST and haplotype distribution) of the Jeju Island population from all other populations does not allow classification of the Jeju roe deer as C. p. tianschanicus (Koh, Yang, Yoo, & Chun, 2000), nor as a distinct subspecies as suggested by Koh and Randi (2001) and Park et al (2014). Siberian roe deer from Jeju Island are indeed different from those of mainland Korea (Lee et al, 2015), but they do not appear to represent a distinct phylogenetic clade, sharing the main haplogroup of Western populations.…”
Section: Taxonomic Status Of Siberian Roe Deer On Jeju Islandmentioning
confidence: 97%
“…In the Republic of Korea, the Siberian roe deer lives on the Korean peninsula and Jeju Island, and is considered a subspecies of Siberian roe deer, Capreolus pygargus tianschanicus Satunin, 1906 [5] or Capreolus pygargus bedifordi Thomas, 1908 [9]. However, several recent genetic and morphological studies have suggested that the roe deer on Jeju Island (Jeju roe deer [JRD]) is different from the roe deer on the Korean peninsula (mainland roe deer [MRD]) [13, 15, 16, 19,20,21]. The JRD has a smaller body and skull than the MRD [19,20,21] and is genetically more similar to populations in western Siberia than those in the Far East [13, 15, 16].…”
mentioning
confidence: 99%
“…However, several recent genetic and morphological studies have suggested that the roe deer on Jeju Island (Jeju roe deer [JRD]) is different from the roe deer on the Korean peninsula (mainland roe deer [MRD]) [13, 15, 16, 19,20,21]. The JRD has a smaller body and skull than the MRD [19,20,21] and is genetically more similar to populations in western Siberia than those in the Far East [13, 15, 16]. Therefore, the possibility that the JRD belongs to the subspecies Capreolus pygargus ochracean , not C. p. tianschanicus , has been suggested [13].…”
mentioning
confidence: 99%
“…To date, considerable morphological and genetic variation among populations of C. pygargus has been recognized [ 19 , 20 , 24 ]. Especially, the population of Jeju Island, which is isolated from the Korean peninsula, is for sure genetically and morphologically distinct from other populations [ 8 , 11 , 12 , 13 ].…”
mentioning
confidence: 99%